STUDI ANALISIS PENGARUH PARTIAL DISCHARGE PADA SKTM TERHADAP KEHANDALAN PENYULANG - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Nowadays, almost all distribution system of medium voltage in Jakarta using underground cable system. The average life of cable over the last 10 years. Because of that total of cable fault in 2013-2015 are 10.273 cases with average 3000 cases per year this cases cause by external and internal interruption. It is represent a defiance to avoid the number of cable fault so it can improve reliability of distribution system. Index reliability in distribution system are SAIDI & SAIFI. Routine check is realy necessary to avoid any failure in the cable system. Internal interruption in underground cbale usually caused by partial discharge activity. Oscillating Wave Test System (OWTS) can record any partial discharge activity in cable by giving testing voltage to cable.